2010
DOI: 10.1590/s0370-44672010000200027
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de prensas de rolos em minério de ferro

Abstract: ResumoO Projeto Minas-Rio, de propriedade da Anglo Ferrous Brazil, prevê a utilização de prensa de rolos para cominuição do undersize do peneiramento (-25,4 mm). Esta é uma aplicação que se torna cada dia mais comum, porém relativamente nova em minério de ferro.Foram realizados estudos no Centro de Pesquisa da Krupp/Polysius na Alemanha, com o objetivo de validar a aplicação de prensa de rolos para minério de ferro, de determinar os principais parâmetros usados no dimensionamento e de avaliar o impacto do aume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…In the present work, the CAPEx was higher for the conventional route, mainly due to the costs in the ancillaries, primarily conveyor belts, electromechanical assembly, and industrial civil works. Route #2 presented a reduction of 10% in CAPEx compared to the conventional route, which agrees with estimates by Ribeiro et al [31] in a trade-off study on the application of roller presses (HPGR) compared to tertiary cone crushing and screening. In this study, the authors demonstrated a reduction of approximately 8% in comparison to the CAPEx.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In the present work, the CAPEx was higher for the conventional route, mainly due to the costs in the ancillaries, primarily conveyor belts, electromechanical assembly, and industrial civil works. Route #2 presented a reduction of 10% in CAPEx compared to the conventional route, which agrees with estimates by Ribeiro et al [31] in a trade-off study on the application of roller presses (HPGR) compared to tertiary cone crushing and screening. In this study, the authors demonstrated a reduction of approximately 8% in comparison to the CAPEx.…”
Section: Resultssupporting
confidence: 88%
“…On the one hand, the moisture content of the ore can affect the performance of the HPGR if it is excessively high, which can lead to a higher wear rate of the rolls, alongside a reduction in throughput. Ribeiro et al [31] demonstrated that a pilot-scale HPGR processing a similar itabirite iron ore can lose up to 10% of its throughput when the moisture content of the ore reaches values as high as 9%. This is expected to be even more critical in the case of Route #4, given the sensitivity of the VRM process in dealing with moist feed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O projeto Minas-Rio emprega Prensas de Rolos na etapa de pré-moagem, substituindo as etapas de britagem terciária e quaternária. Essa escolha foi baseada principalmente na redução do custo de investimento e do consumo energético, na maior estabilidade da operação e na simplificação do circuito, que a prensa de rolos proporciona [2]. A Prensa de Rolos (Figura 1) consiste em dois rolos girando em sentidos opostos: um deles gira sobre um eixo fixo, enquanto o outro se movimenta linearmente.…”
Section: Introductionunclassified